Role of Teacher’s Feedback in Master’s Level Thesis Writing - Basaula, Asmita (Kalika Journal of Multidisciplinary Studies, 2024)
This study explores the pivotal role of teacher’s feedback and guidance in facilitating the accomplishment of thesis writing, identifying and analyzing common benefits or challenges faced by masters level students incorporating teacher feedback into their thesis writing process. This study is employed based on qualitative research principles, using a narrative inquiry approach. For this, I collected the data taking unstructured interview with the three purposively selected students, involved in Masters level thesis writing from Tribhuvan University (TU) affiliated universities. The collected information was thematically analyzed and interpreted using inductive approach of data analysis. The findings of the study reveal that the teacher feedback on the completion of the master’s thesis assumes many-sided traits. First, it greatly enhances the students’ academic writing skills by providing them with definite and workable guidelines on improving their writing skills. These include feedback on structure, coherence, argumentation, and proper use of academic language—all prime necessities for writing a good quality thesis. Second, teacher feedback enables knowledge acquisition through social interaction. This is usually followed by feedback discussion between the teacher and the learner, whereby learners can clarify their understanding of difficult concepts or get guidelines pertaining to the research methodology or even fine-tune ideas. Such interaction not only helps in the acquisition of knowledge but also in developing critical thinking skills. Thirdly, the research showed that teacher feedback begets self-invention—a process wherein learners began to believe more in themselves, and their sense of academic identity became stronger. This is significant in the context of writing a thesis, where independent research by students is expected, and they are supposed to add original ideas in the subject area. This research finally concludes that the relationship between the teacher and the student during the thesis writing process is, in itself, one of transformation. It is not only the quality of the thesis that is affected by this bond, but it has a telling effect on the overall academic and personal growth of the student. Teachers give constructive feedback, thus influencing the way a student approaches learning, research, and writing. Indeed, the findings of this study point to the importance of the nature of the communicative relationship between the teacher and student, and it is suggested that institutions be aware of the necessity of having a context that fosters positive, supportive relationships between students and their supervisors.